(untitled) (Journal of Architectural Design, 2022)
One of the current problems of the world is the process of development of world urban planning and the formation of agglomerations. These processes have been greatly influenced in recent years by the growth of the urban population, its concentration in economically developed large cities, and the strengthening of links between individual cities and villages (both transport, social, domestic, and labor). In recent years, there has been a significant increase in the socio-economic development of the country.